Clinical risk factors of colorectal cancer in patients with serrated polyposis syndrome: a multicentre cohort analysis. Issue 2 (24th November 2015) - IJspeert, J E G; Rana, S A Q; Atkinson, N S S; van Herwaarden, Y J; Bastiaansen, B A J; van Leerdam, M E; Sanduleanu, S; Bisseling, T M; Spaander, M C W; Clark, S K; Meijer, G A; van Lelyveld, N; et al.
Abstract : Objective: Serrated polyposis syndrome (SPS) is accompanied by an increased risk of colorectal cancer (CRC). Patients fulfilling the clinical criteria, as defined by the WHO, have a wide variation in CRC risk. We aimed to assess risk factors for CRC in a large cohort of patients with SPS and to evaluate the risk of CRC during surveillance. Design: In this retrospective cohort analysis, all patients with SPS from seven centres in the Netherlands and two in the UK were enrolled. WHO criteria were used to diagnose SPS. Patients who only fulfilled WHO criterion-2, with IBD and/or a known hereditary CRC syndrome were excluded. Results: In total, 434 patients with SPS were included for analysis; 127 (29.3%) were diagnosed with CRC. In a per-patient analysis ≥1 serrated polyp (SP) with dysplasia (OR 2.07; 95% CI 1.28 to 3.33), ≥1 advanced adenoma (OR 2.30; 95% CI 1.47 to 3.67) and the fulfilment of both WHO criteria 1 and 3 (OR 1.60; 95% CI 1.04 to 2.51) were associated with CRC, while a history of smoking was inversely associated with CRC (OR 0.36; 95% CI 0.23 to 0.56). Overall, 260 patients underwent surveillance after clearing of all relevant lesions, during which two patients were diagnosed with CRC, corresponding to 1.9 events/1000 person-years surveillance (95% CI 0.3 to 6.4). Conclusion: The presence of SPs containing dysplasia, advanced adenomas and/or combined WHO criteria 1 and 3 phenotype is associated with CRC in patients with SPS. Patients with a history of smoking show a lower risk of CRC, possibly due to a different pathogenesis of disease. The risk of developing CRC during surveillance is lower than previously reported in literature, which may reflect a more mature multicentre cohort with less selection bias.